Capital regulation and ownership structure on bank risk - Haron, Razali; Siddika, Aysa (Emerald Publishing Limited, 2019)
Purpose – This paper aims to examine the impact of capital regulation, ownership structure and the degree of ownership concentration on the risk of commercial banks. Design/methodology/approach – This study uses a sample of 565 commercial banks from 52 countries over the period of 2011-2015. A dynamic panel data model estimation using the maximum likelihood with structural equation modelling (SEM) was followed considering the panel nature of this study. Findings – The study found that the increase of capital ratio decreases bank risk and the regulatory pressure increases the risk-taking of the bank. No statistically significant relationship between banks’ ownership structure and risk-taking was found. The concentration of ownership was found negatively associated with bank risk. Finally, the study found that in the long term, bank increases the capital level that decreases the default risk. Originality/value – This study presents an empirical analysis on the global banking system focusing on the Basel Committee member and non-member countries that reflect the implementation of Basel II and Basel III. Therefore, it helps fill the gap in the banking literature on the effect of recent changes in the capital regulation on bank risk. Maximum likelihood with SEM addresses the issue of endogeneity, efficiency and time-invariant variables. Moreover, this study measures the risk by different proxy variables that address total, default and liquidity risks of the banks. Examining from a different perspective of riskmakes the study more robust.